TANGGUNG JAWAB SOSIAL PERUSAHAAN BAGI PERUSAHAAN PENANAMAN MODAL - Herman Setiawan; Redika Regina Cindy; Zulfikri Toguan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Corporate Social Responsibility (CSR) is both a legal obligation and an ethical commitment inherent in every investment company operating in Indonesia as mandated by Law Number 40 of 2007 on Limited Liability Companies and Law Number 25 of 2007 on Investment. This normative study analyzes three key issues, namely the legal construction of CSR within the investment regulatory framework in Indonesia, the implementation mechanism of CSR by investment companies, and the legal implications of investment companies' non-compliance with CSR obligations. The approach employed is a statutory approach and a conceptual approach by examining various regulations, legal doctrines, and relevant academic literature. The results indicate that Indonesia's CSR legal framework has provided a sufficiently adequate normative foundation, yet its implementation still faces serious challenges regarding standard uniformity, oversight mechanisms, and effective legal consequences. This study recommends strengthening operational and measurable CSR technical regulations as an instrument to drive real contributions from investment companies toward sustainable development.